2006
DOI: 10.1524/zpch.2006.220.10.1309
|View full text |Cite
|
Sign up to set email alerts
|

Microviscosity and Micropolarity Effects of Imidazolium Based Ionic Liquids Investigated by Spin Probes Their Diffusion and Spin Exchange

Abstract: Different polar common spin probes (TEMPO, TEMPOL, and CAT-1) as well as 15N spin probes (15N-TEMPO and 15N-TEMPOL-D17) were investigated to get information about microviscosity and micropolarity of ionic liquids. Rotational correlation times and hyperfine coupling constants of the spin probes were obtained by complete simulation of the ESR spectra. Microviscosity effects as shown by the Gierer–Wirtz theory may explain the spin probe behavior. Investigation of spin exchange of TEMPO, TEMPOL, and CAT-1 dissolve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
55
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(61 citation statements)
references
References 60 publications
6
55
0
Order By: Relevance
“…The mobility of stable nitroxide radical provides information on local viscosity and environment, and this approach is widely used in various fields of science, including 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 studies of ILs. [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34] However, in most cases previous CW EPR data were obtained at temperatures close to ambient and well above melting temperatures of corresponding ILs, and only a few works addressed the low temperature regions between glass transition (T g ) and melting (T m ) temperatures.…”
Section: Auxiliary Cw Epr Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The mobility of stable nitroxide radical provides information on local viscosity and environment, and this approach is widely used in various fields of science, including 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 studies of ILs. [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34] However, in most cases previous CW EPR data were obtained at temperatures close to ambient and well above melting temperatures of corresponding ILs, and only a few works addressed the low temperature regions between glass transition (T g ) and melting (T m ) temperatures.…”
Section: Auxiliary Cw Epr Studiesmentioning
confidence: 99%
“…A number of EPR studies in ILs using spin probes have been accomplished, both in neat ILs and in IL/water mixtures. [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34] In particular, it was shown that nanostructuring of ILs in water can be monitored via polaritydependent hyperfine splitting. However, in general, the shape of the nitroxide spectrum was found to be not very sensitive to the effects of nanostructuring, therefore developing other types of probes for heterogeneities in ILs would be a topical task.…”
Section: Introductionmentioning
confidence: 99%
“…The hyperfine coupling spacing of a nitroxide spin probe is a good measure of the polarity of a solvent, 14 and as such, it has been applied to study the polarity of a variety of ILs. 1518 Using the EPR spin probe method, Pergushov et al have detected structural and dynamic heterogeneity in a 1-octyl-3-methylimidazolium tetrafluoroborate solution. 19 In 1992, Noel et al 20 studied the solvation of two nitoxide spin probes, 2,2,6,6-tetramethylpiperidine-1-oxyl (TEMPO) and 4-amino-2,2,6,6-tetramethylpiperidine-1-oxyl (TEMPAMINE), in ionic liquids.…”
Section: Introductionmentioning
confidence: 99%
“…The isotopic marking of the spin probes 15 N-2,2,6,6-tetramethylpiperidin-1-oxyl (TEMPO) and 4-hydroxy-2,2,6,6-tetramethylpiperidin-1-oxyl (TEMPOL) allows the observation of their lateral diffusion in opposite directions in a one-phase system by means of ESR tomography [163]. Figure 13 displays the profiles of the signal amplitudes after 10 and 135 min, respectively, for the diffusion of the spin probes in the ionic liquid butylmethylimidazolium tetrafluoroborate (BuMeImBF 4 ) [163]. By means of the marking the concentration profiles can be assigned unambiguously and specifically for the respective probe including their spatial distribution.…”
Section: Selected Examplesmentioning
confidence: 99%